Dampak Media Sosial terhadap Pemahaman Keagamaan Remaja di Masjid Al-I'tishom Kartasura: The Impact of Social Media on Teenagers' Religious Understanding at the Al-I'tishom Kartasura Mosque - Tawakal Maiwa Al-Hakim; Nabil Gautama Putra; Muhammad Ashif Dliya’ul Masalik; Bagus Satrio Pambudi; Maulana Fahrurrazi; Ahmad Nurrohim (Litera Academica Publishing, 2025)
Social media has increasingly become a primary source of religious information accessed by Muslim adolescents. Religious content delivered through platforms such as TikTok, Instagram, and YouTube tends to be more engaging and easy to understand, which can enhance interest in learning religion. However, not all information available on social media is accurate or derived from qualified sources, potentially leading to shallow, biased, or misleading religious understanding. Based on the literature review, social media exerts both positive and negative influences on the religious comprehension of Muslim youth. Therefore, religious digital literacy and guidance from families, educators, and religious institutions are required to ensure that the process of learning religion through social media remains structured and accountable.